A Flexible Skin Bionic Thermally Comfortable Wearable for Machine Learning‐Facilitated Ultrasensitive Sensing - Di, Pengju; Yuan, Yue; Xiao, Mingyue; Xu, Zhishan; Liu, Yicong; Huang, Chenlin; Xu, Guangyuan; Zhang, Liqun; Wan, Pengbo (Advanced science, 2024)
Tremendous popularity is observed for multifunctional flexible electronics with appealing applications in intelligent electronic skins, human–machine interfaces, and healthcare sensing. However, the reported sensing electronics, mostly can hardly provide ultrasensitive sensing sensitivity, wider sensing range, and robust cycling stability simultaneously, and are limited of efficient heat conduction out from the contacted skin interface after wearing flexible electronics on human skin to satisfy thermal comfort of human skin. Inspired from the ultrasensitive tactile perception microstructure (epidermis/spinosum/signal transmission) of human skin, a flexible comfortably wearable ultrasensitive electronics is hereby prepared from thermal conductive boron nitride nanosheets‐incorporated polyurethane elastomer matrix with MXene nanosheets‐coated surface microdomes as epidermis/spinosum layers assembled with interdigitated electrode as sensing signal transmission layer. It demonstrates appealing sensing performance with ultrasensitive sensitivity (≈288.95 kPa−1), up to 300 kPa sensing range, and up to 20 000 sensing cycles from obvious contact area variation between microdome microstructures and the contact electrode under external compression. Furthermore, the bioinspired electronics present advanced thermal management by timely efficient thermal dissipation out from the contacted skin surface to meet human skin thermal comfort with the incorporated thermal conductive boron nitride nanosheets. Thus, it is vitally promising in wearable artificial electronic skins, intelligent human‐interactive sensing, and personal health management. A flexible skin bionic thermally comfortable wearable is prepared for machine learning‐facilitated ultrasensitive sensing from thermal conductive boron nitride nanosheets‐incorporated polyurethane elastomer substrate with MXene‐coated surface microdomes as epidermis/spinosum layers assembled with contact electrode, featuring ultrahigh sensitivity (up to 288.95 kPa−1), wide sensing range, excellent cycling stability, and outstanding thermal management for wearable healthcare monitoring and intelligent human–machine interaction.